GE_GERICHTE A/1016/1999 vom 14. September 2000 - GE Cour de justice (2000)
ASSURANCE SOCIALE; AM; SEJOUR A L'HOPITAL; DIVISION PRIVEE; CANTON; SUBVENTION; ASSU | Interprétation de l'ATF | LAMAL.41; LAMAL.49